Gene therapy in status epilepticus. (3rd September 2013) - Walker, Matthew C.; Schorge, Stephanie; Kullmann, Dimitri M.; Wykes, Robert C.; Heeroma, Joost H.; Mantoan, Laura
Summary: Gene therapy in human disease has expanded rapidly in recent years with the development of safer and more effective viral vectors, and presents a novel approach to the treatment of epilepsy. Studies in animals models have demonstrated that overexpression of inhibitory peptides can modify seizure threshold, prevent the development of epilepsy, and modify established epilepsy. More recently there has been a flurry of studies using optogenetics in which light‐activated channels expressed in neurons can transiently change neuronal excitability on exposure to light, thereby enabling the development of closed loop systems to detect and stop seizure activity. The treatment of status epilepticus presents its own challenges. Because of both the delay in gene expression following transfection and also the necessity of using focal transfection, there are a limited number of situations in which gene therapy can be used in status epilepticus. One such condition is epilepsia partialis continua (EPC). We have used gene therapy in a model of EPC and have shown that we can "cure" the condition. Recent evidence suggesting that gene therapy targeting subcortical regions can modify generalized or more diffuse epilepsies, indicates that the range of situations in status epilepticus in which gene therapy could be used will expand.